Learning Media Development: FireDroid Application Base on the Android System and Distance Learning - Anton Abdullah; Wildan Nugraha; Sutiyo Sutiyo; Reyvaldo Fajriansyah Setiawan; Muhammad Iqbal Dwi Saputra; Ridho Priyama Putra (Journal of Airport Engineering Technology (JAET), 2021)
The purpose of this research is to design and develop an Android-based learning media application for the Fire Fighting Equipment course at the Diploma Three PPKP Study Program, Palembang Aviation Polytechnic. The research method used is Research and Development (R&D). This stage of research is 1) Potential and problems; 2) Data collection, 3) Product design, 4) Design validation; 5) Design revisions; 6) Product trials; 7) Design revisions; 8). Usage trials; 9) Revision of the final design; 10) Mass products. User satisfaction questionnaires are used in product success analysis to determine user replies. Responders responded strongly to the response interval of 71-80 people (82.6% - 93%) of the 86 answers, a scale of 4 with the category Very Good (A). The expected benefit is that this learning media can be one of the tools in the lecture process at Palembang Aviation Polytechnic. This research is in the form of a Research Results Report and Intellectual Property Copyright.